2016
DOI: 10.1186/s12884-016-1139-x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the WHO SCC on improving adherence to essential practices during childbirth, in resource constrained settings

Abstract: BackgroundIndia accounts for 27 % of world’s neonatal deaths. Although more Indian women deliver in facilities currently than a decade ago, early neonatal mortality has not declined, likely because of insufficient quality of care. The WHO Safe Childbirth Checklist (SCC) was developed to support health workers to perform essential practices known to reduce preventable maternal and new-born deaths around the time of childbirth. Despite promising early research many outstanding questions remain about effectivenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
80
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(93 citation statements)
references
References 21 publications
9
80
1
3
Order By: Relevance
“…Still, several organizations across India are currently testing coaching-centered interventions of various intensities, suggesting that a coaching-based model could be realistic for this context, albeit with fewer facility visits. Jhpiego's SCC implementation across the state of Rajasthan, India, includes facility-based coaching visits every 2 weeks for the first 2 months, followed by 4 once-per-month coaching visits, 35 , 36 and the Technical Support Unit in Uttar Pradesh has implemented monthly coaching visits for a period of 6 months for a childbirth case-sheet 37 , 38 . Given contextual limitations (such as high transfer rates of facility staff across Uttar Pradesh, including CQCs, and the safety concerns and significant distances that prevented the all-female nurse coaches from coaching in facilities after dark), we need more research on how to best structure and customize coaching-centered interventions like the BetterBirth Program in order to achieve and sustain the most effective adoption of essential birth practices.…”
Section: Lessons Learnedmentioning
confidence: 99%
“…Still, several organizations across India are currently testing coaching-centered interventions of various intensities, suggesting that a coaching-based model could be realistic for this context, albeit with fewer facility visits. Jhpiego's SCC implementation across the state of Rajasthan, India, includes facility-based coaching visits every 2 weeks for the first 2 months, followed by 4 once-per-month coaching visits, 35 , 36 and the Technical Support Unit in Uttar Pradesh has implemented monthly coaching visits for a period of 6 months for a childbirth case-sheet 37 , 38 . Given contextual limitations (such as high transfer rates of facility staff across Uttar Pradesh, including CQCs, and the safety concerns and significant distances that prevented the all-female nurse coaches from coaching in facilities after dark), we need more research on how to best structure and customize coaching-centered interventions like the BetterBirth Program in order to achieve and sustain the most effective adoption of essential birth practices.…”
Section: Lessons Learnedmentioning
confidence: 99%
“…Authors of a study to measure effectiveness of SCC conducted in Rajasthan, India found that 2-3% women were properly assessed and appropriately referred at time of admission. 21 The partograph usage in study area ranged from 8-13%. Postintervention, the percentage of appropriate assessment improved to 88% and partograph usage to 52%.…”
Section: Discussionmentioning
confidence: 97%
“…Data was collected six months after the introduction of the SCC at the maternity. Six months was chosen because previous research conducted on the SCC in India [21] showed that adherence to essential birth practices could be evaluated within this period.…”
Section: Methodsmentioning
confidence: 99%
“…It consists of four pause points (or moments of care); on admission, just before pushing or caesarean, within one hour after birth, and shortly before discharge. A study conducted in India in 2016 showed signi cantly improved adherence to practices, six months post-training in the intervention arm [21]. Further, the BetterBirth trial in India reported an increase in providers' adherence to essential birth practices after two months of peer coaching in primary level facilities [22].…”
Section: Introductionmentioning
confidence: 99%